EFFECT OF CLASSROOM SEATING ARRANGEMENTS ON THE STUDENTS’ ACADEMIC ACHIEVEMENT AT SECONDARY SCHOOL LEVEL IN THE SOUTHERN DISTRICTS OF KHYBER PAKHTUNKHWA, PAKISTAN. - Nasir Ali; Li Sen; Yan Li; Abdul Basit Khan; Tanveer Ahmad, (PAKISTAN ISLAMICUS (An International Journal of Islamic & Social Sciences), 2024)
This research article aims to investigate the effect of classroom seating arrangements on students' academic achievement at Secondary School level in the Southern districts of Khyber Pakhtunkhwa, Pakistan. The seating arrangement in a classroom can significantly influence students' engagement, interaction, and overall learning experience. Without proper classroom seating arrangement, the teaching-learning process is incomplete. The study was descriptive in nature. The population of the study consisted of all 10th grade students of Govt. High Schools in Southern districts of Khyber Pakhtunkhwa. Seven hundred respondents were selected as sample from the selected Govt. High Schools in Southern Districts. Respondents were selected by using a simple random sampling technique. Only 10th grade students from 12 schools six male and six female Govt. High Schools in Southern districts—with 348 male and 352 female students were included in this study. The purpose of the study was to determine how classroom seating arrangements affect Secondary School students' academic achievement in Khyber Pakhtunkhwa's southern regions. To facilitate the collection of respondents' responses, a self-made questionnaire was used to collect data. SPSS was used to appropriately analyze the data. The sample size was determined using the formula proposed by John Curry in 1984. For data analysis, percentage, frequency, and linear regression were employed. The results clearly demonstrate that classroom seating arrangements have a significant impact on students’ academic achievement.